THE HYDROGYMNASTIC LIKE A POSSIBILITY IN THE COMBAT OF THE THEORY OF DISCONNECTION (Fiep Bulletin - online, 2014)
With the advance of capitalist system and the necessity of capital accumulation and wealth production aged ones felt kept out of society inside the social context. Nowadays, in the world, many times the difficulties imposed to the aged ones by the system, create physical problems that develop bad physical, mental and social conditions. According to it, as the people grow old, they contract with the world diminish. With the variety of offers for aged, putting them in the way of practice some type of physical activity and mainly, with the participation of the medicine in the prevention, treatment and control of illnesses, with the improvements in social, politics and economic conditions, and with the adoption of a style of life more healthful, they start to long for a bigger life expectancy.This work had as methodology the application of a questionnaire half-structuralized in 40 aged who frequent classes of hydrogymnastic in academies of the north zone of Rio de Janeiro. The physical activity could provide an increase of self-esteem besides approaching the aged one of the social conviviality.  The hydrogymnastic contributes as it pointed in the research with respect to the construction of a friendship circle, what with no doubts diminish considerably with the years. With this, the possibility of the sprouting of the theory of disconnection increases. According that, the increase on their friendship circles and the social importance that hydrogymnastic classes proportioned to the life of the practitioner increases the possibilities of the aged one run away from this theory, making possible a longer life and with a better quality.
Keywords: Aged ones; Hydrogymnastic; Theory of Disconnection